Interior Design of Riau Archipelago Cultural Information with Nautical Identity Approach - Pitrry Putri; Titi Indahyani; Yunida Sofiana (Talenta Publisher, 2026)
The diversity of culture and marine resources of the Riau Archipelago that exist and develop into local wisdom in the community is a potential regional tourism attraction that needs to be preserved. The current generation is less concerned in promoting and preserving the potential of local culture which is a local heritage and identity. The swift movement of globalization have a great influence on the existence of local culture and potential which causes the decrease of understanding, recognition and preservation of the culture. As of now, the facilities that can be used as a means of information about the Riau Archipelago are still inadequate. The purpose and benefits of the design in this study are to provide facilities that serve as a forum to support activities and the need for information and edutainment facilities for visitors. The research methodology used is a qualitative method by carrying out a survey and equipped with a literature study on the concept of local wisdom and cultural information center. The result of this research is the application of a design approach (Mengelana Pesona Bahari) which is dominated by design inspiration that processes in terms of color and form of nautical identity in the Riau Archipelago. As a result, this design is expected to contribute to disseminating and preserving information as well as to spread the culture of the Riau Archipelago and supporting regional tourism.